Apolipoprotein ε4 allele is associated with frailty syndrome: results from the hellenic longitudinal investigation of ageing and diet study. (23rd August 2019) - Mourtzi, Niki; Ntanasi, Eva; Yannakoulia, Mary; Kosmidis, Mary; Anastasiou, Costas; Dardiotis, Efthimios; Hadjigeorgiou, Giorgos; Sakka, Paraskevi; Scarmeas, Nikolaos
Abstract: Apolipoprotein ( APOE ) ε4 allele has been associated with a number of age-related diseases but previous studies failed to identify any link with Frailty syndrome. The aim of the present study is to investigate the association between APOE ε4 allele and frailty syndrome. We operationalised Frailty according to the Fried definition, and we determined the APOE genotype in 1234 participants of the hellenic longitudinal investigation of ageing and diet study. Logistic regression analyses were performed to examine the association between APOE ε4 allele and frailty. Models were adjusted for age, education, sex, presence (or absence) of hypertension, diabetes, myocardial infraction, coronary disease, congestive heart failure, arrhythmia or other heart disease, family history of dementia and current smoking. The same models were performed after exclusion of patients with dementia and participants with APOE ε2/ε4 genotype. In the fully adjusted model, carriers of APOE ε4 allele had 2.753 higher odds of frailty relative to non-carriers. After trichotomization of APOE genotype, APOE ε4 heterozygotes had 2.675 higher risk of frailty compared to non-carriers while exclusion of patients with dementia or/and APOE ε2/ε4 genotype did not alter the association. The APOE ε4 allele may be a significant biomarker of frailty with diagnostic and prognostic capacity.